Psychosocial End-of-Life Considerations for Healthcare Providers - Vazquez, Lauren D (the Academic Division of Ochsner Clinic Foundation, 2011)
This article summarizes concepts related to psychosocial issues at the end of life with special attention directed to the rights of the mentally ill, issues related to mental capacity to consent, and suicidality and desire for hastened death in patients with a terminal illness. We discuss assessment tools and clinical decision-making strategies to guide the healthcare provider in dealing effectively with the often difficult situations involving patients facing the end of life.